(untitled) (Journal of Scientific Research, 2011)
Novel neck-structured Fe3O4, γ-Fe2O3 and α-Fe2O3 magnetic nanoparticles were successfully prepared by a modified hydrothermal method. Ferrous chloride tetrahydrate was solely used as a precursor for the novel nanomaterials. The X-ray diffractometric study revealed the purity of the nanomaterials thus synthesized. All of the products were characterized using a field-emission scanning electron microscope (FE-SEM) and a transmission electron microscope (TEM) for the particle size and morphology. Neck-structured particle morphology was observed for the first time in all of iron oxides with magnetic properties. The particle size observed was 50–60 nm. The synthesized nanomaterials showed excellent magnetization values when magnetic hysteresis loops were measured using a superconducting quantum interference device (SQUID). Moreover, the as-prepared magnetic nanoparticles suspensions showed significant temperature increments under an AC (alternating current) magnetic-field induction condition at room temperature which indicates the hyperthermia feasibility. Keywords: Magnetic materials; Neck-structured; Hyperthermia; Heat dissipation. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i1.8727 J. Sci. Res. 4 (1), 99-107 (2012)